2005
DOI: 10.1111/j.1365-2427.2005.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of protozoan‐ and viral‐mediated mortality of bacterioplankton in Lake Bourget (France)

Abstract: 1. We performed three, 1-week in situ experiments in March-April (expt 1), May (expt 2) and August (expt 3) 2003 in order to assess protozoan and virus-induced mortality of heterotrophic bacteria in a French lake. Viral and bacterial abundances were obtained using flow cytometry (FCM) while protozoa were counted using epifluorescence microscopy (EFM). 2. A dilution approach, applied to pretreated grazer-free samples, allowed us to estimate that viral lysis could be responsible for 60% (expt 1), 35% (expt 2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 90 publications
6
91
1
2
Order By: Relevance
“…In our study, the presence of picocyanobacteria was important and abundant mainly in spring and early summer, when the thermal stratification and clear water phase took place. This corroborates the results found by several authors (Anneville and Leboulanger, 2001;Jacquet et al, 2005;Cellamare et al, 2010) in their research. Recently, it is well known that nutrient availability, sedimentation, and grazing were considered the major driving forces of microbial and algal communities in aquatic environments (Tijdens et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the presence of picocyanobacteria was important and abundant mainly in spring and early summer, when the thermal stratification and clear water phase took place. This corroborates the results found by several authors (Anneville and Leboulanger, 2001;Jacquet et al, 2005;Cellamare et al, 2010) in their research. Recently, it is well known that nutrient availability, sedimentation, and grazing were considered the major driving forces of microbial and algal communities in aquatic environments (Tijdens et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with KtW, those authors concluded that prokaryotic abundance was controlled mainly by protistan grazing, whereas viruses were mostly responsible for changes in the composition of the prokaryotic community (equations 1 to 4). Jacquet et al (42) investigated the temporal variation of prokaryotic mortality due to viruses and grazers in a lake. Those authors found that mortality due to viruses increased and that due to grazers decreased during the summer compared to spring.…”
Section: Combined Effects Of Viral Lysis and Protistan Grazingmentioning
confidence: 99%
“…Viruses, HNF ϫ Prokaryotic and viral abundance, prokaryotic production, inorganic nutrients, community composition of Bacteria and Archaea Zhang et al (113) Viruses, HNF ϫ Prokaryotic abundance and production, community composition of Bacteria and Archaea Jacquet et al (42) Viruses, HNF ϫ Prokaryotic and viral abundance, concn of nutrients, grazing rates, viral infection and burst size Jardillier et al (44) Viruses, HNF ϫ Prokaryotic and viral abundance, abundance of protists, community composition of Bacteria, FISH for distinct prokaryotic groups, prokaryotic production, viral infection of prokaryotes Šimek et al (86) Viruses, HNF eventually having acquired immunity to up to 22 of the tested viruses. At the end of the experiment, the cultures were dominated by strains resistant to either one or both of the viruses present during the incubations, with small populations of sensitive strains maintaining both viruses at abundances of above 10 6 ml Ϫ1 .…”
Section: The Issue Of Resistance To Viral Infectionmentioning
confidence: 99%
“…Cela est en partie dû à ce que ces bactéries ne constituent pas des populations majeures en terme d'abondance quand les bactériophages, des virus infectant les bactéries, eux, peuvent atteindre des densités dix fois supérieures aux populations bactériennes [1]. Les bactéries prédatrices obligatoires de bactéries (c'est-à-dire dépendantes de la prédation pour se reproduire) sont regroupées dans un groupe polyphylétique 1 [8,9]. Ces proportions indiquent que les Peredibacteracées pourraient jouer, de par leur abondance relative, un rôle non négligeable sur la dynamique biologique de leur proie et donc exercer un rôle important dans l'équilibre des grands lacs.…”
Section: Le Monde Méconnu Des Balounclassified